Metals in the service of man - Street, Arthur (Penguin, 1962)
Metallurgical research and industrial techniques are constantly advancing, and this latest edition has been updated to cover a range of developments, from new methods of examining metals and alloys under the electron microscope to the welding of oil rigs under the sea.